Environmental Correlates of Oyster Farming in an Upwelling System: Implication Upon Growth, Biomass Production, Shell Strength and Organic Composition - Garcia-Herrera, C (Elsevier Ltd, 2024)
Comprehending the potential effects of environmental variability on bivalves aquaculture becomes crucial for its sustainability under climate change scenarios, specially in the Humboldt Current System (HCS) where upwelling intensification leading to frequent hypoxia and acidification is expected. In a year-long study, Pacific oysters (Magallana gigas) were monitored at two depths (1.5m, 6.5m) in a bay affected by coastal upwelling. Surface waters exhibited warmer, well-oxygenated conditions and higher chlorophyll-a concentrations, while at depth greater hypoxia and acidification events occur, especially during upwelling. Surface cultured oysters exhibited 60 % larger size and 35% greater weight due to faster growth rate during the initial month of cultivation. The condition index (CI) increases in surface oysters after 10 months, whereas those at the bottom maintain a lower index. Food availability, temperature, and oxygen, correlates with higher growth rates, while pH associates with morphometric variables, indicating that larger oysters tend to develop under higher pH. Increased upwelling generally raises CI, but bottom oysters face stressful conditions such as hypoxia and acidification, resulting in lower performance. However, they acclimate by changing the organic composition of their shells and making them stronger. This study suggests that under intensified upwelling scenario, oysters would grow slowly, resulting in smaller sizes and lower performance, but the challenges may be confronted through complex compensation mechanisms among biomass production and maintenance of the shell structure and function. This poses a significant challenge for the sustainability of the aquaculture industry, emphasizing the need for adaptive strategies to mitigate the effects of climate change. © 2024 Elsevier Ltd